“EL APROVECHAMIENTO DEL “ACUÍFERO GUARANÍ” EN EL ABASTECIMIENTO DE AGUA PARA LA CIUDAD DE CAAGUAZÚ” - Acosta Álvarez, Roberto (Águas Subterrâneas, 2004)
This present study is a resume of hydrogeology study and the abtained results in the building of deep tubular wells built in the area of Caagauzú city where the groundwater Formations Misiones and Independencia occurred. The interpretation of the data allowed stratigraphic regional-local configuration, to know the hydrodynamic’s parameters, geochemistry of the water and, to propose an exploitation criteria which allow the preservation of the groundwater in an over exploitation of the deep-tube well’s battery to cover de demand, to elaborate the adduction project from the location of the deep-tube wells through a meet-box up to the reservoir and the up-tank. At this stage, the project will cover the demand of 37,000 in habitants which means 3,735 connections, for which it necessary to draw out 400 m3/h of groundwater from the Formations Misiones and Independencia subjacent to the region. The factibility studies of the groundwater for the provision potable water for Caaguazú city, covered the stream basin “Toro Blanco”, ”Empalado” and part of the Jhú stream, it was elaborated for Corposana (Essap) with the financial support of Bank Interamerican Development – BID.